Global Ocean Mass Change From GRACE and GRACE Follow‐On and Altimeter and Argo Measurements. Issue 22 (19th November 2020) - Chen, Jianli; Tapley, Byron; Wilson, Clark; Cazenave, Anny; Seo, Ki‐Weon; Kim, Jae‐Seung
Abstract: Satellite altimeter sea surface heights, in combination with Argo ocean temperature and salinity observations, provide an independent measure of global mean ocean mass (GMOM) change. Over the period January 2005 to April 2020, GMOM rates observed by the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow‐On (GFO) range from 1.88 ± 0.10 to 2.63 ± 0.10 mm/year, compared to 2.85 ± 0.37 mm/year from Altimeter‐Argo. Over much of the GRACE era, GRACE GMOM estimates agree well with Altimeter‐Argo over a broadband of frequencies. However, during the late stage of the GRACE mission (after August 2016) and into the GFO era, differences between GRACE/GFO and Altimeter‐Argo GMOM estimates become substantially larger and systematic, which may be related to the single accelerometer mode of operation during late‐stage GRACE and GFO missions and/or errors of Argo and altimeter data. Key Points: GRACE/GFO‐derived global ocean mass change agrees generally well with Altimeter‐Argo estimates at seasonal and long‐term scales The GRACE/GFO and Altimeter‐Argo GMOM differences become substantially larger and systematic during the late‐stage GRACE and GFO periods The discrepancy is likely related to the single accelerometer mode of the late‐stage GRACE and GFO and/or errors of Argo and altimeter data